PENGARUH EFEKTIFITAS PENERAPAN SISTEM PERIZINAN ONLINE, KUALITAS SUMBER DAYA MANUSIA DAN KOMUNIKASI ORGANISASI TERHADAP KUALITAS PERIZINAN PADA UNIT PELAKSANA PELAYANAN TERPADU SATU PINTU KOTA ADMINISTRASI JAKARTA BARAT - Zaini, Zaman; -, Efendi; -, Tuswoyo (Faculty of Social and Political Sciences, Universitas Swadaya Gunung Jati, 2023)
The purpose of this study is to evaluate the magnitude of the effect of the Effectiveness of the Application of the Online Licensing System, the Quality of Human Resources and Communication on the Quality of Licensing Services at the West Jakarta Administrative City One Stop Service Unit.The method of research approach uses descriptive quantitative, the number of samples is 68 people, the research approach used is the method of descriptive quantitative research approach, using the technique of Multiple Linear Regression and Multiple Correlation.Based on the results of the study prove that there is a significant influence between the Effectiveness of the Application of the Online Licensing System, the Quality of Human Resources and Organizational Communication on the Quality of Licensing Services at the West Jakarta Administrative City One Stop Service Unit. From the results of hypothesis testing, it shows that the Fcalculate is 24.292 > Ftable of 3.44, the results of this test mean that Ho is rejected and H1 is accepted. This shows that the Effectiveness of the Application of Online Licensing Systems, Quality of Human Resources and Organizational Communication together to the Quality of Licensing Services in West Jakarta Administrative One-Stop Services Unit Implementing Unit is 53.2% while the remaining 46.8% is influenced by other factors.